2000
DOI: 10.1097/00005344-200005000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolonged Propranolol Treatment on Left Ventricular Remodeling and Oxidative Stress After Myocardial Infarction in Rats

Abstract: Mechanisms determining the benefit of beta blockade in patients with heart failure remain incompletely understood but are assumed consequent to prevention of deleterious effects of catecholamines. Recent studies have demonstrated that oxidative stress in congestive heart failure may be related to increased catecholamine levels. The aim of this study was to examine effects of long-term treatment with propranolol on progression of left ventricular (LV) dysfunction, remodeling and oxidative stress on an experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…In addition to its b-adrenergic antagonist activity, propranolol has antioxidant and anti-inflammatory properties, that are in part linked to the protection of membranes against lipid peroxidation (11). Propranolol reduces intracellular Ca 2 þ overload and attenuate mitochondrial dysfunction by its action on electron mitochondrial membrane transport and also by inhibiting Bax-mediated cytochrome C release (12,13). It also inhibits NADPH oxidase and protein kinase C activity (14) and decreases VEGF/(bFGF) basic fibroblast growth factor genes expression (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its b-adrenergic antagonist activity, propranolol has antioxidant and anti-inflammatory properties, that are in part linked to the protection of membranes against lipid peroxidation (11). Propranolol reduces intracellular Ca 2 þ overload and attenuate mitochondrial dysfunction by its action on electron mitochondrial membrane transport and also by inhibiting Bax-mediated cytochrome C release (12,13). It also inhibits NADPH oxidase and protein kinase C activity (14) and decreases VEGF/(bFGF) basic fibroblast growth factor genes expression (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Propranolol or pindolol did not show free radical scavenging properties relevant for cardioprotection in a coronary occlusion model of isolated hearts of rabbit [660]. However, long-term in vivo treatment with propranolol abolished the increase of oxidative stress and reduced the cardiac sensitivity to catecholamine-induced arrhythmias in infarcted rats [658].…”
Section: Catecholamines and Oxidative Stress: A Complex Talk With Sevmentioning
confidence: 82%
“…I/R is probably the most studied cardiac disease and several drugs have been evaluated using I/R models. The antioxidant properties of propranolol and other -adrenoceptor antagonists are controversial, as some in vitro and in vivo studies support them [421,657,658] while others do not [651,659,660]. Propranolol or pindolol did not show free radical scavenging properties relevant for cardioprotection in a coronary occlusion model of isolated hearts of rabbit [660].…”
Section: Catecholamines and Oxidative Stress: A Complex Talk With Sevmentioning
confidence: 99%
“…Nevertheless, the true relationship between oxidative stress, endothelial damage and CHF is still unknown, although there is ample evidence that oxidative stress is involved in the pathogenesis of atherosclerosis, endothelial damage, platelet aggregation and CHF [32,33]. It is currently thought that excessive production of superoxide may reduce synthesis of endothelium-derived relaxation factor (EDRF) or nitric oxide (NO), while stimulating the release of endothelins [34][35][36][37]. Recent data have also shown a close link between apoptosis and oxidative stress [18].…”
Section: Discussionmentioning
confidence: 99%
“…Kukin et al [34] recently reported that both carvedilol and metoprolol reduced oxidative stress significantly and equally after 6 months therapy. Other β-blockers, such as propanolol [35], have also been shown to reduce oxidative stress indirectly, although propanolol possesses neither cytotoxic nor superoxide-scavenging properties and its membranestabilizing effects may even lead to inhibition of superoxide generation [36].…”
Section: Discussionmentioning
confidence: 99%